MANAJEMEN SISTEM PENJAMINAN MUTU INTERNAL BIDANG AKADEMIK UNTUK MENINGKATKAN MUTU PEMBELAJARAN PADA LEMBAGA PENDIDIKAN SWASTA - Muhammad Lukman; Iim Wasliman; Hanafiah Hanafiah; Yosal Iriantara (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The problem of this research is the management of quality assurance in private educational institutions that has not been maximized. The purposes of this research are (1) planning, (2) implementation (3) evaluation (4) control, (5) development, (6) problems, and (7) problem solutions. The research approach uses qualitative. The results of the research in particular are (1) Quality assurance management planning consisting of indicators of vision and mission, objectives, programs, timelines, monitoring and evaluation plans, and follow-up has been well planned. (2) Implementation of academic quality assurance management in educational institutions. (3) Evaluation of quality assurance management consisting of indicators of evaluation objectives, evaluation tools, evaluation results, and evaluation follow-up plans have been carried out in accordance with applicable standards. (4) Quality assurance management control consists of indicators of control objectives, types of control, and results of control that have been carried out in accordance with SOP. (5) Quality assurance management development consists of development planning indicators, development organization, development implementation, and development evaluation. (6) Problems consisting of indicators of planning, implementation, evaluation, control, and improvement problems still exist but can still be overcome. (7) Problem solutions consisting of planning, implementation, evaluation, control, and improvement problem indicators can be handled properly